2010
DOI: 10.1080/08927014.2010.524297
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms isolated from washing machines from three continents and their tolerance to a standard detergent

Abstract: The goal of this comparative study was to investigate biofilm forming microorganisms living in washing machines (WMs). Biofilms were sampled from 11 washing machines from four countries and three continents. Among the 94 isolated strains, 30% were potential human pathogens. Representative strains were selected and biofilm formation was evaluated with the crystal violet (CV) assay. The majority of the WM isolates formed more biofilm than their reference strains. Biofilms of P. putida WM (the largest biofilm pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 30 publications
2
79
1
6
Order By: Relevance
“…The study of Gattlen et al [8] also found gram-negative Proteobacteria being the predominant phylum inside the washing machine as well. This is also in line with the fact that bacterial biofilms of environmental samples are dominated by Proteobacteria [32 -36].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The study of Gattlen et al [8] also found gram-negative Proteobacteria being the predominant phylum inside the washing machine as well. This is also in line with the fact that bacterial biofilms of environmental samples are dominated by Proteobacteria [32 -36].…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies could show that organisms that were isolated from biofilms from washing machines are more tolerant to chemical detergents compared to control strains [8,15]. For this reason potential drug-resistant organisms, which have been identified in the domestic environment, imply a potential health risk due to cross-contaminations during the washing process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of malodours in the washing machine is due to the biofilm growth [31], an inconvenience that can be The stain required the use of additional specific stain removal products 29.7…”
Section: Critical Issues Of the Washing Processmentioning
confidence: 99%